Mythological and Archetypal Elements in Cinema: An analytical Psychology vView of The princess bride (1987) - Martín Muñoz, Teresa (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The Princess Bride is a cult film packed with symbolic and mythological elements. This study follows the line of works that claim that the fiction projected in films has the potential to help an individual grow in self-awareness and paves the way towards individuation, by making the symbolic elements conscious. (Hauke, 2009; Izod, 2000). From the notion of collective unconscious of C. G. Jung and "the hero's journey” (Campbell, 2017), and through the analysis of the mythological and archetypal content this work offers us an approach to a reading of the fifth art from a profound psychological perspective.